Đáp án + Giải thích các bước giải:
`a)`
`2R + 2H_2O -> 2ROH + H_2` `(1)`
`R_2O + H_2O -> 2ROH` `(2)`
`n_(H_2) = (1,12)/(22,4) = 0,05` `(mol)`
`n_(ROH)(1) = n_R = 2n_(H_2) = 2 . 0,05 = 0,1` `(mol)`
`-> n_(ROH)(2) = 0,6 - 0,1 = 0,5` `(mol)`
Thấy : `n_(R_2O) = n_(ROH)(2) . 1/2 = (0,5)/2 = 0,25` `(mol)`
Theo bài ra :
`m_R + m_(R_2O) = 17,8`
`-> 0,1R + 0,25 . (2R + 16) = 17,8`
`-> 0,6R + 4 = 17,8`
`-> R = 23`
Vậy `R` là `Na`
`b)` Giả sử `m_R = 17,8` (tức chỉ không có `R_2O`)
Khi đó : `n_R = n_(ROH) = 0,6` `(mol)`
`-> R = (17,8)/(0,6) = 29,67` `(1)`
Giả sử `m_(R_2O) = 17,8` (không có `R` trong hh)
`n_(R_2O) = 2n_(ROH) = 0,6 . 1/2 = 0,3` `(mol)`
`-> 2R + 16 = (17,8)/(0,3) = 59,33`
`-> R = 21,67` `(2)`
`(1) ; (2) -> 21,67 < R < 29,67`
`-> R= 23` thỏa mãn